Program PDS UPI dalam Pendidikan Jasmani: Membumikan Penjas Bernuansa Mendidik - Mahendra, Agus (Prodi PGSD Penjas FPOK UPI, 2018)
Physical Education lesson in school still displays a typical impression that deliver a particular feeling coveying that PE is hard, stiff, and often rough and creepy. As the consequence, children in the PE lesson take an indifferent attitude or enjoy it all by being what is expected from the said situations. The LD UPI program for PE in Elementary Schools became a catalyst for the paradigm shift at the school, especially for respected in-service PE teachers, and at the same time for students who were undertaking the internship program as pre-service teachers. With directly seeing the lecturers' actions in teaching for over 8 times repetition, it was believed that the paradigm change has taken place as has been expected, and it was accompanied by changes and improvements in teaching skills, in addition to strengthening their mastery of pedagogical content knowledge. This manuscript is a resume of best practices generated from the LDS in PE program, which can be used as a reference both for improving teachersâ€™ teaching competencies in Schools, and for reconstructing the PETE program curriculum at Higher Learning level.Â AbstrakPenjas di Sekolah masih menampilkan wajah yang keras, kaku, bahkan sering kasar dan menyeramkan. Sebagai konsekuensinya, anak dalam pelajaran Penjas mengambil sikap tidak peduli atau sekalian menikmatinya dengan menjadi apa yang seolah diharapkan dari Penjas demikian. Program PDS UPI untuk Penjas di Sekolah Dasar, menjadi katalisator bagi upaya perubahan paradigm Penjas di sekolah, terutama bagi para guru Penjas dalam jabatan, dan sekaligus bagi para mahasiswa yang sedang melakukan PPL serta guru Pra-Jabatan. Dengan melihat aksi dosen dalam mengajar yang berulang hingga 8 kali pertemuan, diyakini perubahan paradigm itu sekaligus diiringi perubahan dan peningkatan keterampilan mengajar, di samping memantapkan penguasaan mereka terhadap pedagogical content knowledge. Naskah ini merupakan sebuah paparan best-practices yang dihasilkan dari program PDS Penjas di Lab School UPI, yang dapat dijadikan rujukan baik bagi peningkatan kompetensi mengajar guru di Sekolah, maupun bagi penyempurnaan kurikulum program PETE di PT.Â